THE INFLUENCE OF V DIAGRAM PROCEDURAL SCAFFOLDING IN GROUP INVESTIGATION TOWARDS STUDENTS WITH HIGH AND LOW PRIOR KNOWLEDGE (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
The learning achievement of high school students of Malang city in physics was still low, thus the appropriate learning strategies was necessaryto optimize the physics learning achievement. V diagram procedural scaffoldingin Group Investigation was designed with the aim to optimize student learning achievement. The purpose of this study was to examine differences in learning achievement of groups of students who learn through Scaffolding Procedural strategies in Group Investigation and groups of students who are studying with Group Investigation, to examine differences in student achievement between thosewith high and low prior knowledge levels, and to examine the interaction between learning strategies (procedural scaffolding in GI and GI) and initial knowledge of students towardlearning achievement. The method used in this study wasquasi-experimental.The design used in this study was Two Factorial Design consisted of two experimental classes and two control classes each. The results indicated that learning achievement group of students who learn through proceduralscaffolding in Group Investigation was higher than the group of students who are studying with Group Investigation. The learning achievements of students with high prior knowledge surpassed those with low prior knowledge. Last, there was an interaction between the learning strategies and prior knowledge of students toward learning achievement.